TRAINING PROTOCOL ON CHANGES IN GLYCEMIC LEVELS AND BLOOD PRESSURE IN INDIVIDUALS WITH TYPE 1 DIABETES - Camilo, Victor Fernandes; Costa, Matheus André Ribeiro da; Vitória, Estela Urzêda; Sudré, Tamyris Mendes de Faria; Xavier, Larissa Rebeca Luz; Oliveira, Rodrigo Franco de (CIPEEX, 2025)
Type 1 Diabetes Mellitus (T1DM) is an endocrine condition resulting from the autoimmune destruction of pancreatic beta cells, leading to severe insulin deficiency. Clinically, T1DM manifests with symptoms such as polyuria, polydipsia, xerostomia, unexplained weight loss, fatigue, polyphagia, and blurred vision. Glycemic self-monitoring is a critical process for these patients, allowing the measurement of glucose in different contexts such as home, school, and work environments, and adjusting the insulin dose as needed. According to data from the International Diabetes Federation, in 2019, Brazil ranked fifth globally in terms of diabetes prevalence, with 16.8 million adults affected in the age group of 20 to 79 years. The American Diabetes Association recommends that adults with T1DM participate in at least 150 minutes per week of moderate to vigorous intensity physical activities. For children and adolescents with T1DM, the practice of at least 60 minutes daily of physical activities is recommended, including muscle and bone strengthening exercises three times a week. Regular physical activity is associated with a reduction in the risk of future cardiovascular diseases, improved long-term glycemic control, better cardiovascular conditioning, quality of life, reduction in daily insulin needs, and better weight control. Furthermore, it plays a crucial role in the primary and secondary prevention of cardiovascular diseases related to diabetes. This study aims to evaluate the effects of strength training on glycemic parameters after an exercise session in adults with T1DM.